1967
DOI: 10.1002/macp.1967.021010119
|View full text |Cite
|
Sign up to set email alerts
|

Über den aufbau von polyurethan‐kunststoffen. II. Die struktur von polyurethan‐schaumstoffen in abhängigkeit von der temperatur, der zeit und der rezeptur; IR‐spektroskopische nachweisgrenzen für urethan‐ und harnstoffgruppen in polymeren

Abstract: ZUSAMMENFASSUNG:Friihere IR-spektroskopische Untersuchungen an Polyurethan-Schaumstoffen werden auf das Temperaturverhalten der Schaumstoffe, a d Beziehungen zwischen Struktur und Rezeptur sowie auf die zeitliche Reihenfolge der in Frage kommenden Reaktionen ausgedehnt. Bei erhohter Temperatur werden freie Isocyanatgruppen iiber Carbodiimide in deren Polymerisate umgewandelt. Die Biuretgruppen in einem Schaumstoff werden iiber die Spaltung in Harnstoffgruppen und freies Isocyanat abgebaut, letzteres reagiert i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1970
1970
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…However, a number of discrepancies in the literature redirected our attention to this class of compounds, whose importance in the chemistry of polyurethanes is so great. For instance, Merten et al [1][2][3] found no absorption at 1640 cm-' in the infrared spectrum of a polyurethane foam produced with the aid of water and attributed this to a secondary reaction of the polyurea with isocyanate to form the biuret. An attempt, using model compounds and analogous conditions, to reproduce such a secondary reaction to form the biuret was, however, unsuccessful.…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of discrepancies in the literature redirected our attention to this class of compounds, whose importance in the chemistry of polyurethanes is so great. For instance, Merten et al [1][2][3] found no absorption at 1640 cm-' in the infrared spectrum of a polyurethane foam produced with the aid of water and attributed this to a secondary reaction of the polyurea with isocyanate to form the biuret. An attempt, using model compounds and analogous conditions, to reproduce such a secondary reaction to form the biuret was, however, unsuccessful.…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of the carbodiimide band reached its maximum at 280 8C and decreased at higher temperatures because monomeric car- bodiimide (Eq. (4)) converted into polymeric carbodiimide structures 20) . Besides the decrease of the carbodiimide absorption, the carbodiimide polymerization is also recognizable by a broadening of the absorption of the polymeric structures at 1 613 cm -1 which is vaguely seen in the 290 8C curve in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In I R spectra of unexposed polyu rethane ( F igure 1) the absorption bands characteristic of the urethane functional group [ 10,11 ] IR spectra of irradiated solutions ( Figure 1) show the decrease of intensity of absorption bands mentioned above and shift of the carbonyl band from 1700 cm-1 to 1730 cm-l . As the photolysis proceeded the intensity of the bands of the urethane group decreased whereas the band at 1730 crri became at the same time stronger.…”
Section: Resultsmentioning
confidence: 99%